IMPLEMENTASI KRIPTOSISTEM KURVA ELIPTIK PADA DATA AUDIO DIGITAL - Anita Ahmad Kasim (Jurnal Teknomatika, 2011)
Technology not only allows information submitted in the form of text, but also in the form of images, audio or video. However, the use of digital audio data is not necessarily improves the security of the message. Various attack techniques emerged so others can know the confidential information contained in digital audio messages. One attempt to provide information that can be done is a cryptographic system or cryptosystem. In the elliptic curve equation are the values that can be used as a private key and public key to encrypt the data in this form of audio. Audio data will be processed on the secure encryption and decryption using elliptic curve cryptography. Parameters and variables contained in the curve equation would be calculated to determine the shared secret key to be used in both encryption and decryption process audio. The conditions before the encrypted audio data are audible. The result of encrypting the audio data to produce a new audio is not clear. Decryption process causes the data back to the original audio data so that the second audio data can be heard clearly. Attack man in the middle of this process can’t decrypt the encrypted audio file. File decryption results may not be tuned so that the audio file will be secure and can only be heard by the user encryption and decryption that really has the right combination of keys that user actual encryption and decryption.